Differences in Physical Demands Among Offensive and Defensive Players in Elite Men Bandy. Issue 4 (2nd October 2021) - Persson, Emil; Andersson, Marcus; Blomqvist, Sven
ABSTRACT: Purpose : This study examined the physiological sport-specific demands (total distance, mean velocity, effective game time, and time in five velocity zones) in elite bandy players of offensive and defensive playing positions. Method : Data were collected with 10 Hz GPS-units in the Swedish Elite League during the season 2015/16. Ten male elite bandy players were examined during 13 matches. Data were analyzed with Independent Samples Test and with descriptive statistics. Result : Analysis showed that defensive positions covered a significantly longer ( p < .001) total distance (23.2 ± 2.4 km vs 21.1 ± 3.5 km) compared to the offensive positions. Significantly higher ( p < .001) mean velocity was found in offensive positions (17.8 ± 1.0 km/h vs 15.5 ± 1.6 km/h) in relation to defensive positions. In variable effective game time analysis exposed significant differences ( p < .001) between offensive positions and defensive positions (90.4 ± 3.5 min vs 71.3 ± 11.9 min). Furthermore, in easy and moderate skating defensive positions spent significantly ( p < .001) more time and in fast, very fast, and sprint skating offensive positions spent significantly ( p < .001) more time in relation to each other. The descriptive analysis of positions indicates that libero, defender, and half have the longest game time, half skate the longest distance, and forward have the highest mean velocity during the game. Conclusion : From a practical perspective, the result can provide coaches knowledge when planning the setup in training drills. Thus, the training sessions could be more specific to the playing position, which could maximize the player's physiological outcome in order to optimize performance.